دور أخلاقيات البحث العلمي و تأثيرها على جودة البحوث العلمية (مجلة الواحات للبحوث والدراسات, 2020)
Being aware and adhering to the scientific research ethics   and to comply  to all its principles is an essential input to ensure  the quality and effectiveness of a scientific research, this aforementioned   that  was and still is the  direct  reason to establish   a scientific revolution that the world has witnessed in all fields of life, and therefore  , values  of  scientific  research are fundamental principles for scholars and researchers  to respect  and comply  during a  scientific work.    From this perspective, the researcher can acquire ethical behaviour that motivates him doing the right thing and the adequate conduct in the right place and the right time, furthermore to ensure the quality of the scientific research and the scientific researcher’s integrity. Keywords – Ethics - Quality - Scientific Research - Principles – Knowledge